Kebolehan Menolak Wathi’ bagi Istri tanpa Nafkah - Rahmawati, Nurul; Wusqo, Urwatul (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research departs from the phenomenon of a husband's inability to provide for his wife and family which resulted in a change in roles in earning a living. This adds to a wife's obligations because she has to serve her husband, such as inviting him to have sexual intercourse known as wathi'. This research aims to review the ability to refuse an invitation for sexual intercourse or wathi' for a wife whose income is not met. This study includes qualitative research and library research whose data was obtained through various written sources such as books, journals, and news articles regarding husband-wife obligations. The results of this research are the ability of a wife to refuse a wathi' invitation from her husband if the husband is negligent in fulfilling his obligations towards his wife.